Bilingual Education in Rural Islamic High Schools: Teachers' and Students' Perspectives and Experiences - Nirmalasari, Putri; Salija, Kisman; Jafar, Muhammad Basri (Tamaddun Life, 2023)
The purpose of this study is to investigate the perceptions of bilingual teaching held by both teachers and students, as well as the processes used to conduct bilingual language instruction and the results obtained from using bilingual language education. The qualitative research approach was utilized for this investigation. For the purpose of this study, a teacher and ten students from the XI IBB Man 2 Bone Class served as participants and served as the study's subjects. In addition to that, the data gathering was done by a combination of observation, interviews, and documentation. The findings indicated that teachers and students had a favorable impression of bilingual education, placing it in the category of highly perceived bilingual education. The incorporation of bilingual education, which is soundly founded on Baker's theory (2001), comprises the separation of language and the concurrent use of language inside a lesson. Last but not least, there was a beneficial effect that teaching students in two languages has on the overall accomplishment of such students. The present study implies that the bilingual education approach could foster students' EFL repertoires in the context of Senior high school students and specifically within rural regions, as evidenced by the study.